Automated Classroom Attendance in Educational Environments Using a BLE-Based Context-Aware Middleware - Vieira, Emanuel de Franceschi; Rizzetti, Tiago Antônio; Azevedo, Renato Preigschadt De (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2026: Anais do XVIII Simpósio Brasileiro de Computação Ubíqua e PervasivaDO - 10.5753/sbcup.2026.23393, 2026)
This paper presents a context-aware middleware for educational environments that uses Bluetooth Low Energy (BLE) signals to infer room-level presence and support pervasive applications. The architecture integrates ESP32 devices with ESPresense firmware, MQTT communication, Home Assistant for contextual interpretation, and a Python-based middleware responsible for filtering, persisting, and exposing contextual events through a REST API. To validate the proposal, an automated classroom attendance application was implemented on top of this infrastructure. The evaluation was conducted through three controlled simulation runs of 60 minutes each, involving 30 synthetic students and pseudo-random mobility patterns. Results showed stable operation, no WebSocket failures, and coherent attendance behavior across arrival, stay, and departure phases. Although 21,600 MQTT messages were published per run, only 14.38% generated persisted events, indicating effective noise reduction by the middleware compared to a raw-event persistence baseline. During the stay phase, the average attendance reached 27.43 out of 30 students (91.43%). The paper also discusses privacy, deployment cost, hardware portability, and limitations of BLE-only presence sensing in real classrooms.